KETERAMPILAN KONSELING BERBASIS METAKOGNISI - Radjah, Carolina Ligya (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research aims to describe the characteristics and metacognition of high school counselors. The type of research used is descriptive with a survey method. The research subjects were 166 school counselors. The research results show that the counseling process has not fully implemented metacognition-based counseling skills. This indicates that in implementing counseling, counselors have not taken into account the effectiveness of intrapersonal skills as an integrated skill within the counselor.